.Jamu Potential as Tourism Attraction of Sukoharjo, Central Java – A Review - Hendri Gigih Saputro; Annisa Noor Rachmawati; Putra Pratomo Hadi (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Sukoharjo Regency holds considerable potential to be developed as a jamu-based tourism destination by utilizing its cultural heritage and the community's expertise in traditional herbal medicine. This study finds that the integration of cultural preservation, product innovation, and digital promotion is crucial in strengthening the identity of Sukoharjo as the "City of Jamu." The existence of the Jamu Tourism Village, especially in Nguter Village, has provided a foundation that can be expanded through collaborative efforts among stakeholders. Based on these findings, several practical recommendations can be made. First, the local government needs to formulate supportive policies and provide incentives for jamu MSMEs to synergize with the tourism sector. Second, jamu tourism managers, such as those in Nguter Village, are advised to adopt integrated digital promotion models and offer jamu products as part of bundled wellness tourism services. Additionally, capacity-building programs for the community are necessary to improve service quality and ensure sustainable tourism management. Future research directions may include further studies on tourist perceptions of jamu tourism and its attraction elements, as well as quantitative studies to measure the economic impact of jamu tourism development on local businesses. Ethnographic research is also important to document the still-living traditional practices of jamu in the community, ensuring that cultural knowledge is preserved and passed down to future generations.